Alpha‐momorcharin preserves catalase activity to inhibit viral infection by disrupting the 2b–CAT interaction in Solanum lycopersicum. (15th November 2022) - Yang, Ting; Peng, Qiding; Lin, Honghui; Xi, Dehui
Abstract: Many host factors of plants are used by viruses to facilitate viral infection. However, little is known about how alpha‐momorcharin (αMMC) counters virus‐mediated attack strategies in tomato. Our present research revealed that the 2b protein of cucumber mosaic virus (CMV) directly interacted with catalases (CATs) and inhibited their activities. Further analysis revealed that transcription levels of catalase were induced by CMV infection and that virus accumulation increased in CAT‐silenced or 2b‐overexpressing tomato plants compared with that in control plants, suggesting that the interaction between 2b and catalase facilitated the accumulation of CMV in hosts. However, both CMV accumulation and viral symptoms were reduced in αMMC transgenic tomato plants, indicating that αMMC engaged in an antiviral role in the plant response to CMV infection. Molecular experimental analysis demonstrated that αMMC interfered with the interactions between catalases and 2b in a competitive manner, with the expression of αMMC inhibited by CMV infection. We further demonstrated that the inhibition of catalase activity by 2b was weakened by αMMC. Accordingly, αMMC transgenic plants exhibited a greater ability to maintain redox homeostasis than wild‐type plants when infected with CMV. Altogether, these results reveal that αMMC retains catalase activity to inhibit CMV infection by subverting the interaction between 2b and catalase in tomato. Abstract : Alpha‐momorcharin directly disrupts the interaction between catalase and 2b by competing with 2b in binding to catalases, altering cellular redox homeostasis, reducing toxic reactive oxygen species production, and augmenting resistance against cucumber mosaic virus infection.